Understanding of Social Media Literacy About Malay Cultural Teaching: A Case Study of Students of SMAIT Al-Ittihad Pekanbaru - M, Trie Khairunnisa; Amelia, Vita; Monika, Winda (Lentera Pustaka: Jurnal Kajian Ilmu Perpustakaan, Informasi dan Kearsipan, 2025)
Background: This research, titled "Understanding of Social Media Literacy Regarding Malay Cultural Teachings: A Case Study of SMAIT Al-Ittihad Pekanbaru Students," aims to investigate the level of social media literacy among students regarding Malay cultural teachings. Social media literacy is crucial in preserving Malay culture in the digital era. An individual's ability to search for, evaluate, and utilize relevant information on social media is essential to understanding and appreciating their own culture.Objective: This study aims to determine the understanding of social media literacy regarding Malay cultural teachings among SMAIT Al-Ittihad Pekanbaru students by using the Big Six model of information literacy, which integrates information search and use skills with the use of technology in a systematic process to locate, use, evaluate, and communicate information for specific purposes and tasks.Methods: This research employed a quantitative descriptive design. Data was collected using questionnaires and observations. The population of this study was 12th-grade students of SMAIT Al-Ittihad Pekanbaru, totaling 104 students. Purposive sampling was used to select a sample of 103 students. Data analysis was conducted using a calculation based on relative frequency distribution. The sampling technique used in this study was purposive sampling. This technique involves selecting research samples based on certain considerations, aiming for the data obtained to be more representative. The sample for this study consisted of 103 12th-grade students from SMAIT Al-Ittihad Pekanbaru who met specific criteria. The criteria for selecting the research sample were: (1) Students of SMAIT Al-Ittihad Pekanbaru who had already taken the Riau Malay Culture subject, specifically the material on Tunjung Ajar Melayu: "Bercapak bersetinah, berunding berestabik; Be open-minded, open-handed; Know how to listen, be good at interpreting; Win in losing; Know how to live, know how to die inherit" (Speaking with wisdom, discussing with respect; Open-minded, generous; Able to listen, good at concluding; Winning in defeat; Knowing how to leave behind a legacy in life, knowing how to die in death). (2) Students who have an Instagram account.Results: Based on the research findings and data analysis, the understanding of social media literacy regarding Malay cultural teachings in a case study of SMAIT Al-Ittihad Pekanbaru students was 68.34% in the high category, with the following breakdown: (1) Problem formulation was 82.4%, falling into the very high category. (2) Information search strategy was 74.67%, categorized as high. (3) Location and access was 74.16%, categorized as high. (4) Using information was 56.65%, categorized as moderate. (5) Synthesis was 49.95%, categorized as moderate. (6) Evaluation was 77.25%, categorized as high.Conclusion: This study concludes that the overall understanding of social media literacy regarding Malay cultural teachings among SMAIT Al-Ittihad Pekanbaru students is in the high category, with a score of 68.34%. The highest competence lies in the "problem formulation" aspect (82.4%), while the lowest is found in the "synthesis" aspect (49.95%). These findings indicate that while students are proficient in identifying and searching for information, they need further development in processing and re-presenting the information, particularly in synthesizing cultural values from social media content. This underscores the importance of targeted educational interventions to strengthen students' abilities to interpret and communicate cultural knowledge effectively in the digital age.